Silencing of hydroxycinnamoyl-coenzyme A shikimate/quinate hydroxycinnamoyltransferase affects phenylpropanoid biosynthesis - Hoffmann, L; Besseau, S; Geoffroy, P; Ritzenthaler, C; Meyer, D; Lapierre, C; Pollet, B; Legrand, M (The Plant cell, 2004)
The hydroxyl group in the 3-position of the phenylpropanoid compounds is introduced at the level of coumarate shikimate/quinate esters, whose synthesis implicates an acyltransferase activity. Specific antibodies raised against the recombinant tobacco (Nicotiana tabacum) acyltransferase revealed the accumulation of the enzyme in stem vascular tissues of tobacco, in accordance with a putative role in lignification. For functional analysis, the acyltransferase gene was silenced in Arabidopsis thaliana and N. benthamiana by RNA-mediated posttranscriptional gene silencing. In Arabidopsis, gene silencing resulted in a dwarf phenotype and changes in lignin composition as indicated by histochemical staining. An in-depth study of silenced N. benthamiana plants by immunological, histochemical, and chemical methods revealed the impact of acyltransferase silencing on soluble phenylpropanoids and lignin content and composition. In particular, a decrease in syringyl units and an increase in p-hydroxyphenyl units were recorded. Enzyme immunolocalization by confocal microscopy showed a correlation between enzyme accumulation levels and lignin composition in vascular cells. These results demonstrate the function of the acyltransferase in phenylpropanoid biosynthesis.